The Struggle Of Love As Reflected In Nicholas Spark’s The Notebook - Harisa Mandasari; Feby Meuthia Yusuf (Fakultas Sastra Universitas Ekasakti, 2017)
The notebook is a romantic novel by literary writer Nicholas Sparks. The analysis focuses on the story line narrated by Noah Calhoun. Noah is a young man from a poor family, Noah is in love with Allie a girl from a wealthy family. This research uses a structural approach. This approach is a pure approach to literature mixing other disciplines into the discussion. The theory used is the extrinsic theory of literature itself, and is also supported by the flow theory where the character Noah Calhoun seeking his true love. This study also uses structural methods, in which all data is only analyzed in the elements that make up the literary works themselves, such as grooves and characterizations. In this study the authors found: (1) Noah left Allie because Allie's parents did not approve of their love story, and Noah decided to go to war. Allie's parents did not approve of their relationship because noah was born from a poor family. And Allie's parents set her up with another man. (2) Noah's love affair occurs when Noah reunites with Allie and new problems arise when Allie is already fiancee with another man. Problems can be seen when the relationship is contrary to the parent because of the difference in status. But Allie kept making sense to Noah about her parents' decisions. (3) when Noah returns with Allie after Allie realizes that she loves Noah over Lon and after Allie's parents see her daughter's love for Noah they finally agree on the relationship. This novel tells about the love of the first story that turned into true love. And this novel tells about how a character Noah to be able to maintain his first love despite many obstacles.